Experimental argumentation of development of force and force-velocity abilities of judo players in the context of coaching process - Manolachi, V. (Journal of Physical Education and Sport, 2015)
The paper presents the research regarding the study of the dynamics of ability development of judo players in the context of current and timely correction of the training process during the four years of pedagogical research. The force and force-velocity abilities of athlelets were studied based on following informative tests: the strength of the back lumbar muscles; thigh muscle strength; calf muscle force; biceps force; triceps force; leg muscle explosive force; five throws over the back; five throws back and front with an obstacle; climbing 4m on headfast. The prior pedagogical observations (performed during two years) have shown the formation of a trend regarding the positive influence of the timely correction process of training on effective growth of most indices that characterize the abilities of force and force-velocity of judo players. The final results of the pedagogical experiment confirmed the significant and continuous growth of the studied capacity in the context of timely correction of the training process.